The Role of ODM (Oil Discharge Monitoring) in Preventing Oil Pollution Referring to MARPOL Rules 73/78 Annex I - Akhmad Ndori; Astri Kustina Dewi; Riza Nur Amala; Sarlita Inka Saputri Yuliani (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
An oil spill at sea is the release of oil, either directly or indirectly, into the marine environment originating from shipping activities, oil and gas business activities, or other activities. In order to handle and prevent pollution due to oil spills, the IMO (International Maritime Organization) has made regulations that must be implemented in the world of international shipping. MARPOL Regulation 73/78 Annex 1 is a regulation issued to overcome this. In implementing this regulation, ships are required to have equipment in the form of an Oil Discharger Monitor (ODM). This tool functions as a monitor of activities in the process of disposing of waste into the sea by ships. So in this study the researcher wants to discuss the role of ODM (oil discharger monitor) in preventing marine pollution in accordance with MARPOL 73/28 Annex I standards.